2014
DOI: 10.1007/s00213-013-3422-0
|View full text |Cite
|
Sign up to set email alerts
|

Quetiapine extended-release (Seroquel-XR) versus amitriptyline monotherapy for treating patients with fibromyalgia: a 16-week, randomized, flexible-dose, open-label trial

Abstract: Our results appear to indicate that quetiapine XR does not provide similar efficacy to amitriptyline for treating patients with fibromyalgia. Quetiapine XR had a worse tolerability than amitriptyline in this population, possibly due to a relatively high starting dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0
5

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 39 publications
(21 citation statements)
references
References 19 publications
0
16
0
5
Order By: Relevance
“…A statistical analysis indicated that quetiapine had failed to prove non-inferiority compared to amitriptyline. Moreover, 51% of the subjects in the quetiapine arm of the study withdrew prior to completion, mostly due to adverse effects [16]. In an earlier smaller study quetiapine or placebo (NCT00983320) was added to other pharmacologic treatments for FMS.…”
Section: Quetiapinementioning
confidence: 99%
“…A statistical analysis indicated that quetiapine had failed to prove non-inferiority compared to amitriptyline. Moreover, 51% of the subjects in the quetiapine arm of the study withdrew prior to completion, mostly due to adverse effects [16]. In an earlier smaller study quetiapine or placebo (NCT00983320) was added to other pharmacologic treatments for FMS.…”
Section: Quetiapinementioning
confidence: 99%
“…Potential clinical benefits include an analgesic effect, anxiety reduction, and establishment of normal sleep patterns, all of which are associated with and worsen FGID symptoms including pain. Most data stems from the treatment of fibromyalgia where recently a controlled study reported effects superior to placebo on the pain‐domains, but with effects inferior to duloxetine in yet another recent study . A major drawback is poor tolerability with a high proportion of patients experiencing sedation, dizziness and weight gain leading to discontinuation of treatment when used in the higher dose ranges of 100–300 mg/day.…”
Section: Augmentation Treatmentmentioning
confidence: 99%
“…Amitriptyline was found to reduce the FIQ questionnaire results from baseline to endpoint by over 30% [48][49][50]. It was found to improve pain, fatigue, sleep, and quality of life [11].…”
Section: Tricyclic Antidepressants (Tcas) Although Differentmentioning
confidence: 98%